SOSIALISASI PENGGUNAAN MEDIA SOSIAL INSTAGRAM DALAM MEMPROMOSIKAN WISATA ANTON TELU DESA SESAOT - Nurhikmah Nurhikmah; Inang Irma Rezkillah; I Dewa Putu Bagiartha; Nurhalisah Nurhalisah; Niken Suari; Pattimatuzzohrah Pattimatuzzohrah; Wahyu Malajusammar (Jurnal Abdi Insani, 2023)
Sesaot Village is one of the villages that has many tourist attractions such as Aik Nyet tourism, Tibu Top Waterfall, and Bunut ngengkang bath. The number of tourist villages in Sesaot village that are already known by the wider community but there are still wisat places in Sesaot that are not known by the community. One of the less well-known tourist attractions by the community is the anton telu tour. Lack of promotion of tourist attractions and more focus on their culinary advantages. Online media is a choice as a means of promotion, especially Instagram, considering the number of internet users is increasing all the time. The purpose of socialisation is to provide knowledge and direction to the public to introduce Instagram social media as a means to promote Anton Telu's tourism. The location of the socialisation activity is in Anton telu tourism, West Lombok, Narmada District, West Nusa Tenggara Province by involving eleven sesaot village communities with educational socialisation using discussion methods, questions and answers, practical use of social media. The result of socialisation activities is that the Sesaot village community specifically around Anton Telu tourist attractions gets knowledge about the benefits of promoting tourist attractions that are managed on social media. In addition, the Sesaot village community gets knowledge about image and video editing techniques to make them look attractive when promoted and promotional strategies on social media, especially Instagram. From this activity, it can be concluded that the implementation of the activity went well because of the cooperation with various parties at the target location, namely, the head of the village of Sesaot, the manager of the Anton Telu tourist attractions, and the target masayrakat and the Sesaot village community, expect further socialisation related to the use of applications to make videos and images to support the promotion of Anton telu tourist attractions.